Allosteric modulators enhance agonist efficacy by increasing the residence time of a GPCR in the active state - Anne-Marinette Cao (Nature Portfolio, 2021)
Here, the authors use smFRET to assess the structural dynamics of metabotropic glutamate receptor mGlu2 and show that a positive allosteric modulator or the Gi protein stabilize mGlu2 in the glutamate-induced active state, leading to the full activation of the receptor.